Network determinants of a collaborative funding system: The case of the German innovation policy - Florian Umlauf (Philipps-University Marburg, Department of Geography, 2014)
The granting of publicly subsidized joint projects has become a popular policy instrument in Germany and other developed countries. However, little is known about how an emerging subsidization network affects the overall allocation process of further project grants. Employing a database that contains all funded R&D projects of the German federal government, this paper analyzes the extent to which the funding network tends to reproduce itself. The results of an empirical model show that participation within a collaborative project does not raise, per se, the chance of an enterprise obtaining another project grant. Rather, it is important to hold central positions within the network or have access to a diverse external knowledge base to receive anew project grant.
Keywords: H32; L53; L60; O38; 330; R&D subsidies; project allocation; network determinants; cooperation